Building Reminder Receivables Through Bki Reminder Application As A New Innovation And Company Business Solution At The Semarang Commercial Pratama Branch Bumn Holding Survey Services (Survey Id) - Ismail; Eko Sakapurnama; Rachma Fitriati (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
PT. The Indonesian Classification Bureau (Persero) or better known as BKI, has a very large amount of receivables . The large amount of BKI's receivables was caused by the difficulty of the client's ability to pay debts and also the difficulty of the receivables collection PIC team in remitting the receivables to the client. To reduce the amount of receivables, efforts are being made to digitize the receivables collection process. Previously, receivables collection was done manually, so clients did not receive regular receivables reminders due to officers not being optimal in carrying out receivables reminders. Accounts receivable reminder officers have various job descriptions and the large amount of receivables makes the officers overwhelmed. So receivable reminders need to be done digitally using the BKI Reminder Application. This application can send receivables reminders automatically via email and Whatsapp and can monitor the condition of receivables. The receivables database is taken from SAP by synchronizing the receivables reminder application with SAP so that the data is presented in real time and can simplify the receivables collection process. By using Soft Systems Methodology (SSM), this study aims to make receivables collection easier, that is, officers do not need to manually remit receivables. Receivable reminders are carried out automatically by the application at the Pratama Komersil Semarang Branch which can improve operational efficiency and service quality. The results of the study show that to overcome this problem, the Pratama Komersil Semarang Branch requires the application of digital technology through the BKI Reminder Application. In this way, receivables reminders become more effective and efficient in responding to the challenges of Industry 4.0 in order to increase BKI's competitiveness as a leader in the maritime sector